Evaluating the Effectiveness of Self and Peer Assessment using PBL on Student Performance and Preference: Malaysians Experience (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
This paper reports on the effectiveness of students performances between self and peer assessment based on students preferences. A total of 56 respondents from the second year of study at UTeM who enrolled for the Human Computer Interaction course took part in this study. Three research instruments were developed for the purpose of evaluating students performance and preferences which include a set of questionnaires, interview questions and prototype development. A t-test was conducted to analyze independent variables by self and peer assessment while students preferences and performances are dependent variables. Findings of this study revealed that students prefer peer assessment rather than self assessment. The use of courseware namely PBLAssess can increase students understanding towards the topic that has been taught. Results showed that assessment in PBL is significantly related to students performances and preferences.